2012
DOI: 10.1051/0004-6361/201118725
|View full text |Cite
|
Sign up to set email alerts
|

The discovery of a shell-like event in the O-type star HD 120678

Abstract: Aims. We report the detection of a shell-like event in the Oe-type star HD 120678. Methods. HD 120678 has been intensively observed as part of a high-resolution spectroscopic monitoring program of southern Galactic O stars and Wolf-Rayet stars of the nitrogen sequence.Results. An optical spectrogram of HD 120678 obtained in June 2008 shows strong H and He i absorption lines instead of the double-peaked emission profiles observed both previously and subsequently, as well as a variety of previously undetected ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 38 publications
0
18
1
1
Order By: Relevance
“…They suggested that these sources could be a wind-colliding binary system. Gamen et al (2012) showed that stars can change their spectra within months.…”
Section: Appendix A: Spectral Classification Of Emission-line Starsmentioning
confidence: 99%
“…They suggested that these sources could be a wind-colliding binary system. Gamen et al (2012) showed that stars can change their spectra within months.…”
Section: Appendix A: Spectral Classification Of Emission-line Starsmentioning
confidence: 99%
“…Gamen et al (2008) revised the classification of the main-sequence O5 to O5III(f) and mentioned that it is actually a binary with a 5.9 d period and minimum masses of 31 and 15 M .…”
Section: Hm1mentioning
confidence: 99%
“…VB10 (XID 7) was classified as O5V by Massey et al (2001), but its nature was recently revised: it is a binary of type O5III(f)+OB, with a period of 5.9d, and minimum masses of 31 + 15 M (Gamen et al 2008). Amongst the three X-ray bright O-stars, VB10 is the hardest and brightest (log [L X /L BOL ] = −7.0).…”
Section: Detected O-starsmentioning
confidence: 99%
“…The project will include further high-angular resolution imaging, multiple-epoch R ∼ 40 000 optical spectroscopy (Gamen et al 2008), a recalibration of the intrinsic colors for hot stars and the extinction law , and a combination of spectroscopic and trigonometric parallaxes . Regarding high-resolution imaging, the goal is to eventually observe ∼500 massive stars with AstraLux and, if a similar instrument becomes available in the Southern hemisphere, to observe another ∼500 stars from there, in all cases using the Galactic O-Star Catalog (Maíz Apellániz et al 2004;Sota et al 2008) to select the sample.…”
Section: Overall Strategymentioning
confidence: 99%